Innovative development of regions and internal migration in Russia - S. N. Apenko; A. V. Lukash (E-Management, 2023)
The article considers internal migration and its connection with innovative transformations in the subjects of the Russian Federation from 2016 to 2021. The relevance of the topic is due to the need to overcome the negative trends associated with the constant outflow of the economically active population from some regions of the country. The purpose of the article is to establish the strength of statistical relationship between the interregional movement of labor resources and the key indicators that reveal the innovation potential of the subjects of the Russian Federation. The following tasks were solved: internal and interregional migration of able–bodied population was analyzed; federal districts with a positive and negative difference between incoming and outgoing able–bodied population were identified; the dynamics of interregional movement in the context of migration causes was examined, including the most common of them for the period from 2016 to 2021. The article uses general scientific methods of research, as well as statistical analysis of migration movement data within the country and indicators of the rating of innovative development of regions. The novelty of the work is related to the comparison of regional labor migration and aggregated assessments of economic, educational, digital and institutional development of the regions. As a result of the study it was found that to assess the strength of the statistical relationship between the migration activity of the population of the country’s regions and their position, respectively, in the ratings of aggregate innovative development with such indicators as the Russian regional Innovation Index (hereinafter referred to as the RRII); the index of socio–economic conditions of innovation activity (hereinafter referred to as the ISEC); the index of the quality of innovation policy (hereinafter referred to as the - IQIP), it can be both medium (for RRI) and weakly expressed (for ISEC and IQIP).